Determinan Minat Beli Produk Secara Online di Supermarket Hypermart Gorontalo - Arifin Arifin; Rahmisyari Rahmisyari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This research aims to analyze and determine the magnitude of the influence of perceived security, ease of transactions, trust and shopping experience on interest in buying products online at Hypermart Gorontalo. The research sample consisted of 90 people using a questionnaire as a data collection tool and using Path Analysis as a data analysis method. The results of the research show that Perception of Security (X1), Ease of Transaction (X2), Trust (X3) and Shopping Experience simultaneously influence online Purchase Interest (Y) at Hypermart Gorontalo by 0.502 (50.2%), which is 0.498 ( 49.8%) influenced by external variables that were not studied. Perception of Security (X1) partially has a positive and insignificant effect on Purchase Intention (Y), Ease of Transaction partially has a negative and insignificant influence on Purchase Intention (Y), Trust (X3) partially has a significant and influence on Purchase Intention (Y) , and Shopping Experience partially and significantly influences buying interest (Y).